STRATEGI INTEGRASI PEMASARAN PADA DESTINASI WISATA CANDI SOJIWAN - Edy Budiyanto; Muhammad Subkhan; Sri Diana (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This research, actually has two major aims namely: (1) to identified potencies those are have in Sojiwan Temple Tourism Area; (2) to formulate integrated marketing strategic to enhance the number of tourist visits in Sojiwan Temple Tourism Area. To achieve the objectives, the research methods used qualitative methods. The research methods used is rasionalistic paradigm. The qualitative analysis used in this research are observation, in-depth interviews, and Focus Group Discussion. After data has collected, it will clarify with analyses needs. The findings of this research reveals: (1) that the Sojiwan Temple Tourism Area has a great potencies to develop, not only the Sojiwan Temple, but also it nature and cultural tourism; (2) integrated marketing strategic that sould be done in Sojiwan Temple Tourism Area are: determining target market, accomodating customer needs, and planning integrated marketing. Integrated marketing is very important to develop Sojiwan Temple Tourism Area, to enhance the number of visits, and to improve local revenue in Klaten District. Thus they have to having regards to the preservation because Sojiwan Temple Tourism Area is a heritage sites. Based on these findings, this research has some recommendation to the Klaten Government, the communities of Kebondalem Kidul, private sectors, and the other research. The development priority, preferable use tourism attraction development that educational basically and should be more directed towards community involvement in its management, because tourism is the industry that is involving public, private sectors, and community.